URGENSI SIKAP SYAJA’AH DALAM KEPEMIMPINAN: MEMBANGUN PEMIMPIN YANG BERANI DAN BERINTEGRITAS: (The Urgency of Syaja’ah Attitude in Leadership: Building Brave and Integrity Leaders) - Syalima Azura Fitrah (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2024)
The attitude of syaja'ah, which signifies courage in action and facing challenges, is a crucial quality for effective leadership. This article explores the urgency of syaja'ah in modern leadership, highlighting how this trait can build leaders who are both brave and possess integrity. Through a comprehensive literature review and case study analysis, it is found that leaders who embody syaja'ah are better equipped to handle uncertainties, make difficult decisions, and maintain integrity under pressure. These findings indicate that integrating syaja'ah into leadership education and training programs is essential. Courageous leaders not only inspire trust and confidence among their followers but also drive innovation and uphold ethical standards, even when facing significant challenges. In an era marked by rapid change and complex challenges, the need for leaders with syaja'ah is more urgent than ever.Moreover, the presence of syaja'ah in leadership is associated with increased organizational resilience and adaptability. Leaders who display courage can effectively navigate crises and promote a culture of transparency and accountability. This article aims to provide a deeper understanding of the critical role of syaja'ah in leadership and offers practical recommendations for fostering this essential quality in current and future leaders. By integrating syaja'ah into leadership development initiatives, organizations can establish a foundation for more resilient, ethical, and effective leadership that can navigate the complexities of the modern world.